Hen: Queer Puppet Cabaret, Utopian Perspectives for Sexual Bodies - Hirel , Antoine (Nordic Theatre Studies, 2023)
Named after the gender-neutral Swedish pronoun, Hen is a queer puppet show, created and performed by the French artist Johanny Bert. In this performance, the body of the puppet, made of wood, foam and, fabric, is used like a “jigsaw” - assembling different pieces together in order to create and reveal a form, an image, a meaning. It becomes the material for a new vision of how we conceive and construct the body, as it deconstructs essentializing, binary, heteronormative identities, envisioning greater possibilities and pluralities of bodies. Through the vision of non-human object in the space of a theatre, Johanny Bert unveils and rethinks the relationship sexuality and society maintain together by showing sexuality as a theatrical utopia where new forms of bodies and desires can be revealed. Guided by an interdisciplinary approach combining both Gender Studies and Visual Studies, this article talks about how the plasticity of the puppetting object can affect the perception of our own bodies. How and where does the show Hen manifest utopia for the human body and sexuality? Johanny Bert puts the concept of anthropomorphism as the threshold for questioning human sexuality into the theatre and challenges the ways we define and circumscribe bodies and desires, inviting new perspectives for sexual and corporeal paradigms, too.